The influence of different external cooling methods on thermoregulatory responses before and after intense intermittent exercise in the heat - Mitchell, J. B.; Schiller, E. R.; Miller, J. R.; Dugas, J. P. (The Journal of Strength and Conditioning Research, 2001)
The purpose of this study was to determine the effect of different cooling methods on thermoregulation before and after intermittent anaerobic exercise in the heat (38° C). On separate days, 10 men completed 4 conditions consisting of 2 sets of six 30-second sprints (with 30 seconds of rest) at 125% of maximal aerobic power with each set of sprints followed by a cooling procedure. The 4 conditions were the following: passive cooling at room temperature (22° C; PRC), fan cooling (4.0 m;pds1, 22° C; FAC), fan cooling with water spraying (50 ml;pdmin1; FWC), and a noncooling passive recovery in the heat chamber (38° C; PCC). Each set of 6 sprints was followed by a 12-minute cooling period; after the second 12-minute period, cooling continued until esophageal temperature (Tes) was reduced by 1.0° C. Tes and mean skin temperatures (Tsk) were taken before and during exercise and during all cooling phases. Cooling rates (mean ± SEM) after the second set of sprints (based on Tes) were greater (p < 0.05) in PRC (0.043 ± 0.007) than in the other conditions (FWC = 0.027° ± 0.005°, FAC = 0.03° ± 0.004°, and PCC = 0.021° ± 0.003° C per minute). Overall decreases in heat content, however, were greater in the FWC (332.2 ± 27.8) and FAC (129.9 ± 14.7 kJ) conditions compared with the PRC condition (29.0 ± 14.9 kJ). The time required to lower Tes by 1.0° C with PRC (22.8 ± 1.8) was less than with FAC (30.4 ± 2.7 minutes). Finally, the rate of increase in Tes during the second set of sprints was less in the FAC and FWC conditions (0.15° ± 0.01° and 0.11° ± 0.01° C per minute) compared with the PCC and PRC conditions (0.19° ± 0.01° and 0.18° ± 0.01° C per minute), suggesting differences in pre-exercise cooling. Based on cooling rates and the time required to lower Tes by 1.0° C, PRC was the most effective method of cooling. The conclusion is different, however, when taking into account changes in heat content since the FAC and FWC conditions were more effective in dissipating heat and in preventing heat gain during the second set of sprints.